Hereditary Sensory and Autonomic Neuropathy Type VIII (Indian Journal of Case Reports, 2016)
Hereditary sensory and autonomic neuropathy type VIII (HSAN 8 or HSAN VIII) is a rare genetic disorder that usually begins in infancy and is characterized by an inability to feel pain and inability to sweat (anhidrosis). The sensory loss in individuals with HSAN VIII is due to abnormal functioning of the sensory nerves that control responses to pain and temperature. Anhidrosis can cause recurrent episodes of fever and high body temperature. An inability to feel pain can lead to unintentional self-mutilation, repeated fractures, and joint damage. Affected individuals and especially children or infants may be unaware of injury delaying treatment. HSAN VIII is caused by mutations in the PRDM12 gene which is essential for human pain perception.